The Influence Of The Ministry of Youth and Sports of the Republic of Indonesia Program For The Youth Ship Nusantara Sail Karimata 2016 On Youth Nationalism And National Insights In Indonesia - Mutohhari Nasution, Mutohhari Nasution; Badaruddin, Badaruddin; Trimurni Maas, Linda (Publisher Cv. Inara, 2022)
The purpose of this study was to determine the effect of the Indonesian Ministry of Youth and Sports Ship Youth Nusantara program on the sense of Youth Nationalism, the influence of the Indonesian Ministry of Youth and Sports Ship Youth Nusantara program on National Insight. The research method used is descriptive quantitative by using the average test and multiple regression test. The results showed that the influence of the Nusantara Youth Ship Program (X1) on Youth Nationalism (Y1) showed that the X1 variable had a significant effect on Youth Nationalism (Y1), the Nusantara Youth Ship Program (X1) on National Insight (Y2) showed its value was greater than ( 0.05), then the basic provisions of the partial test of the Pemuda Nusantara Ship (X1) do not have a significant effect on National Insight (Y2).